Novel use of plasma pen ablation for the treatment of extensive periocular xanthogranuloma: A case report - Hala M. Nassim Ali; Mohammed M. Alismail; Hissah S. AlTurki; Basheer Aldajani (American Journal of Ophthalmology Case Reports)
Purpose: This case demonstrates a novel technique for treatment of periocular xanthogranuloma using plasma pen ablation, a non-invasive therapy that stimulates skin regeneration. It is used in various conditions, such as benign skin growth removal and non-surgical blepharoplasty, but, to our knowledge, this is the first reported case of periocular xanthogranuloma treated with this method. Observations: A 45-year-old male with dyslipidemia presented with bilateral extensive periocular xanthogranuloma slowly progressing over 10 years, resistant to steroid injection and bleomycin, with positive Touton giant cells on biopsy. The patient underwent 2 procedures, 1 year apart, involving partial excision to achieve 1.5 mm lesion thickness followed by plasma pen ablation with an acupuncture tip. A 12-month and 6-month follow-up after the first and second procedures, respectively, showed effective cosmetic and functional improvement, minimal recurrence, and no notable complications. Conclusion and importance: Due to the extensive and irregular distribution of the lesions, traditional full-thickness excision and skin grafting was not feasible in all affected areas. Thus, a plasma pen was utilized. Plasma pen ablation offers a promising new approach in the management of extensive periocular and primary simple xanthogranuloma. Further research is encouraged to validate these findings.